Application of hypertension clinical guidelines among family medicine doctors in primary health care centers in Riyadh City, Saudi Arabia - Abdulaziz Alhussain; Tarek El Said; Abdulmajeed Aloraini; Abdulelah Alhussain; Turki B. Alqahtani; Mostafa Kofi (Journal of Family Medicine and Primary Care)
Background: Effective management of hypertension relies on adherence to evidence-based clinical practice guidelines (CPGs) among healthcare providers. However, adherence to hypertension CPGs and the factors influencing it among primary care physicians in Riyadh, Saudi Arabia, remain poorly understood. Methodology: This descriptive cross-sectional study aimed to assess the knowledge, application, and determinants of adherence to hypertension CPGs among primary care physicians working in Prince Sultan Military Medical City (PSMMC) and its affiliated primary health care centers in Riyadh, Saudi Arabia. A comprehensive sample of 211 primary care physicians was enrolled, and data were collected using a self-administered questionnaire covering demographic characteristics, adherence to hypertension CPGs, and barriers to guideline application. Descriptive statistics and appropriate statistical tests were used for data analysis. Results: The demographic profile of participants revealed a comprehensive representation of age, marital status, nationality, job title, qualification, and years of practice. The majority of participants demonstrated acceptable levels of knowledge (76.3%) and application (89.1%) of hypertension CPGs. However, barriers related to patient nonadherence to lifestyle modifications and medications were reported, highlighting challenges in implementing guideline recommendations in clinical practice. Significant associations were found between nationality, job title, qualification, and adherence to CPGs, with non-Saudi nationality and junior physicians exhibiting higher rates of unacceptable knowledge and application. Moreover, differences in adherence were observed among physicians following different hypertension CPGs. Conclusion: While primary care physicians in Riyadh demonstrate a strong foundation in evidence-based hypertension management, addressing barriers and disparities in adherence to CPGs requires targeted interventions and collaborative efforts. Promoting a culture of evidence-based practice, enhancing patient education and engagement strategies, and fostering collaboration among stakeholders are essential steps toward improving hypertension control and prevention in the region.